Avaliação das características físico-químicas e microbiológicas de hambúrgueres de frangos suplementados com folhas de oliveiras - Silva, Suelem Lima da (2014)
Chicken meat, due to the high concentration of unsaturated fatty acids, beyond very manipulated in the preparation of meat products, is highly susceptible to oxidation and microbiological growth, which limit its stability and shel-life. The use of natural antioxidants, such as olive leaves, are an alternative in prevention these problems, and allows the use of residues from olive harvest. The objective of this study was to evaluate during storage period of 120 days at -18 ° C, physico-chemical and microbiological characteristics of burgers with chicken breast meat that received olive leaves in their diets. Added in different concentrations of ration olive leaves, being T1 (without olive leaves and addition of sodium erythorbate), T2 (5g olive leaves/ kg feed) e T3 (10g olive leaves/ kg feed). The chicken meat was processed in the form of burgers, plastic bags permeable to oxygen packaged and stored to -18 ºC for 120 days. Were performed pH, fatty acids, lipid oxidation (conjugated dienes, peroxides and TBARS), protein oxidation (carbonyl), instrumental color, proximate composition, water activity and microbiological evaluation (mesophilic, psychrotrophic, enterobactérias and staphylococcus spp.). No significant changes (p> 0,05) in pH, water activity and proximate composition in raw and cooked samples. The fatty acids profile and lipid oxidation were influenced by the olive leaves in the feed (p< 0.05), already not protein oxidation (p> 0.05). Mesophile, psychrotrophic, enterobactérias and staphylococcus spp., treatments containing olive leaves showed significant effect (p <0.05) compared to the development of these bacteria in raw burgers. In the analysis of objective color, treatments with olive leaves not affect the L* and a* variables, but the variable b* yes. There, hamburgers with chicken breast supplemented with olive leaves showed the lowest evolution of oxidative lipidic reactions and microbial growth.